Personality Type Based Pumping-HR Model Toward Working Targets of The Civil Service - Amir Tengku Ramly, Didong Suherbi (Jurnal Manajemen, 2020)
Personality is one of the factors that will affect employee performance. Civil Servants (PNS) who have individual personalities such as introverts and or extroverts can affect employee performance at certain levels. This study shows that employee personality affects their performance. Also, to examine the effect of employee personality on performance based on SKP (Employee Performance Targets). The results showed that there were significant differences between personality types on employee performance. It is found that the kind of personality Extrovert = Introvert produces the best average return based on the SKP evaluation results. In contrast, Extrovert's personality type provides the lowest average in the performance of Civil Servants, in the Agriculture Office of the City of Bogor. The excellent performance in the Regional Work Unit (SKPD), it is recommended to place employees with extrovert = introvert personality types, especially in essential positions.